Fan power and capital in JKT48’s senbatsu sousenkyo voting contest - Prasetyo, Mario Aditya; Angeliqa, Fitria (Universitas Bunda Mulia, 2025)
Senbatsu Sousenkyo (SSK), adapted from Japanese idol sister groups, is an event that members JKT48 and fans look forward to. Through a voting system, fans play a role in determining which members will take center position in the next single. SSK as a general election always experiences a surge compared to the previous event. This shows the militancy of fans which has implications for the popularity of their idols. It cannot be denied that there are various capitals massively empowered to boost voting results. This research aims to explore the complex interactions and contestations of capital in popular culture, especially in the context of participatory democracy in SSK. This research also aims to identify the dominant forms of capital, explore the habitus displayed by fans, and analyze the doxa of the SSK competition arena as a reflection of power dynamics in popular culture. This research uses Pierre Bourdieu's approach in understanding the SSK phenomenon through the trilogy of habitus, field, and capital to analyze how fan practices reproduce power relations in digital fandom economies. This research uses qualitative approach with a case study design. Data collection techniques in this research involved document tracing, non-participatory observation, and analysis of physical artifacts on several fanbase accounts, such as @FreyanationID and @C_Jessination48. This research finds that various capitals in SSK interact with each other to determine the outcome of contestation through, especially economic capital as the main factor in the voting system that boosts voting preferences for certain idols. The victory obtained through the mobilization of economic capital also raises other capitals such as symbolic and social capital related to the ‘closeness’ and previlege obtained by fans. These findings indicate that SSK is a capital-driven battleground that reinforces consumerist culture, produces fan hierarchies, and institutionalizes economic stratification within the idol group entertainment industry.